Epidemiological study of oral squamous cell carcinoma: A hospital based study in Dhaka city - Hossain, Md Abul; Ahmed, Md Mahiuddin; Rahman, AFM Shahidur; Haider, Md Nasim; Alam, AKM Serajul (TAJ: Journal of Teachers Association, 2018)
Objective: To find out the prevalence of oral squamous cell carcinoma among the tertiary and specialized level hospital in Dhaka city Materials and methods: A cross sectional study was carried out in the department of Oral and Maxillofacial surgery of DDCH, NICRH, BSMMU and ShSMCH from january2009 to july 2010 .A total of 324 patient of histopatholgically proven cases of oscc were selected as a sample size. Both primary and secondary data were collected for the study. The prevalence OSCC were calculated by dividing the OSCC patient by total number of patient multiplying 100. Results: The total prevalence of OSCC 3.55% among the 4 tertiary and specialized level hospital in Dhaka city. Conclusion: The prevalence of OSCC among tertiary and specialized level hospital of Dhaka city was 3.55%.The rate is quite high. The prevalence of risk factor includes betel quit, smokeless tobacco, smoking and poor oral hygiene mas also high. The majority of the patient were present in advance stage of the diseases. TAJ 2015; 28(2): 22-25